Image analysis to quantify morphological changes in granular sludge induced by nitrate in EGSB reactors - Araya-Kroff, P. (2004)
Four EGSB reactors (R1 to R4) were operated at an organic loading rate of 10 kgCOD/(m³.d), hydraulic retention time of 3.6 h, upflow velocity of 10 m/h and different influent nitrate concentrations (0, 20, 60 and 100 mgN-NO_3-/L for R1, R2, R3 and R4, respectively. After about 20 days of operation, the granular sludge was characterized for: (i) morphology by quantitative image analysis; (ii) specific methanogenic activity in the presence of acetate, propionate, butyrate, ethanol and H_2/CO_2; (iii) settling velocity. LfA parameter, defined as the ratio of total filaments length to total projected area, was determined and was sensitive to quantify the different surface morphology, induced by nitrate to the granular sludge. Although the growth of filamentous structures was evident, no significant decrease on the settling velocity was observed, most likely because granules grew during the trial period. A higher washout occurred in R4, as compared to R1, R2 and R3.